Exploring potential of exosomes drug delivery system in the treatment of cancer: Advances and prospective - Deepika Yadav; Rishabha Malviya (Elsevier, 2023)
Exosomes are vital for cellular communication and the transfer of materials between cells. Recently, it has been shown that nanoparticles may be used as diagnostic indicators and as a potential medicine delivery strategy due to their nanoscale size and capacity to carry biological components to target cells. Exosomes have the potential to be an appealing and practical approach for drug administration in cancer treatment due to their biocompatibility, high stability, favoured tumour homing, and adjustable targeting efficacy. While exosomes have properties that make them useful for transporting bioactive compounds, the gap between our present understanding of exosome biology and the most optimal condition for their use remains. The rationale for using exosomes as a drug delivery strategy, their production and purification, bioengineering and targeting, uptake and distribution, efficacy, immune response, and other factors will all be discussed in this study. Modern methods are required for observing, categorising, and sorting exosome diversity. Improvements in nanotechnology and our knowledge of exosome biology will undoubtedly speed up the field's medical uses.